Effects of flash-dried poultry protein and select menhaden fish meal on growth performance of weanling pigs - Moser, S.A.; Woodworth, J.C.; Grinstead, G.S.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 180 pigs (l2.961b and 21 d of age) was used in a 28 d trial to determine the effects of substituting flash-dried poultry protein for select menhaden fish meal in the phase II diet on the performance of weanling pigs. Five dietary treatments were fed from d 7 to d 28 after weaning (phase II). Select menhaden fish meal (2.5 and 5%) and flash-dried poultry protein (2.85 and 5.70/0) replaced soybean meal in the control diet on a lysine basis. Pigs fed the diets containing select menhaden fish meal and flash-dried poultry protein had similar ADG and ADFI; however, neither protein source improved performance when compared to the control diet. Further research must be conducted in a field environment in order to determine if fish meal and poultry protein will express a greater response compared to the control diet.
Keywords: Swine; Poultry protein; Fish meal